2023
DOI: 10.1093/jmcb/mjad072
|View full text |Cite
|
Sign up to set email alerts
|

JunB condensation attenuates vascular endothelial damage under hyperglycemic condition

Xuxia Ren,
Zexu Cui,
Qiaoqiao Zhang
et al.

Abstract: Endothelial damage is the initial and crucial factor in the occurrence and development of vascular complications in diabetic patients, contributing to morbidity and mortality. Although hyperglycemia has been identified as a damaging effector, the detailed mechanisms remain elusive. In this study, identified by ATAC-seq and RNA-seq, JunB reverses the inhibition of proliferation and the promotion of apoptosis in human umbilical vein endothelial cells treated with high glucose, mainly through the cell cycle and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 131 publications
0
1
0
Order By: Relevance
“… 9 , 10 Since our FRAP assays mainly showed a dynamic turnover of Aurora-A on the beads and centrosomes rather than its LLPS behavior in vivo ( Figures 1 F–1I), we also fused the FUS-IDR domain with the Aurora-A LLPS-deficient mutants, and explored the localizations and the rescue effects of the FUS-IDR fused mutants to further study the LLPS behavior of Aurora-A. By introducing the N-terminal of FUS (IDR region, 1-214aa), which is highly disordered and widely used to add into candidate LLPS-deficient mutants to study the behavior and function of the candidate condensate in vivo or in vitro , 62 , 63 , 64 to the Aurora-A mutant 11A and R46D, both Aurora-A-FUSN-11A and Aurora-A-FUSN-R46D partially restored the phase separation of Aurora-A and rescued the deficiency in MT polymerization caused by Aurora-A RNAi and promoted the PLK1 phosphorylation, referring that the phase separation of Aurora-A contributed to its mitotic centrosome functions ( Figures 4 H–4K). Thus, our data suggested that the LLPS of Aurora-A promoted centrosome maturation, centrosome separation, MT assembly from centrosomes and its kinase activity.…”
Section: Resultsmentioning
confidence: 99%
“… 9 , 10 Since our FRAP assays mainly showed a dynamic turnover of Aurora-A on the beads and centrosomes rather than its LLPS behavior in vivo ( Figures 1 F–1I), we also fused the FUS-IDR domain with the Aurora-A LLPS-deficient mutants, and explored the localizations and the rescue effects of the FUS-IDR fused mutants to further study the LLPS behavior of Aurora-A. By introducing the N-terminal of FUS (IDR region, 1-214aa), which is highly disordered and widely used to add into candidate LLPS-deficient mutants to study the behavior and function of the candidate condensate in vivo or in vitro , 62 , 63 , 64 to the Aurora-A mutant 11A and R46D, both Aurora-A-FUSN-11A and Aurora-A-FUSN-R46D partially restored the phase separation of Aurora-A and rescued the deficiency in MT polymerization caused by Aurora-A RNAi and promoted the PLK1 phosphorylation, referring that the phase separation of Aurora-A contributed to its mitotic centrosome functions ( Figures 4 H–4K). Thus, our data suggested that the LLPS of Aurora-A promoted centrosome maturation, centrosome separation, MT assembly from centrosomes and its kinase activity.…”
Section: Resultsmentioning
confidence: 99%